Performance Analysis of Prefabricated Steel-Spring Floating-Slab Track and Its Application to Urban Express Rail Transit - Xudong Huang; Ping Li; Xinwei Luo; Liang Ling; Abdulmumin Ahmed Shuaibu; Zhiping Zeng (Advances in Civil Engineering)
The aim of the research is the design of prefabricated steel-spring floating-slab track to be applied in urban express rail transit systems. Using a developed vehicle-track dynamic-coupling equation for steel-spring floating-slab track, the effects of length, thickness, vertical damping, and use of side-mounted isolators on the floating-slab track were investigated experimentally using full-scale model and under different working conditions. The finding of the study revealed the following: (1) The prefabricated steel-spring floating-slab track can be applied to urban express rail transit, because it meets the requirements of high-speed transit while efficiently reducing noise. (2) The floating-slab track’s stability slightly increases with the increase of its length and thickness. As thickness increases, vertical displacement of the rail increases slightly, and lateral stability increases, thereby slightly improving the vehicle’s running stability. (3) When the intercity electric multiple-unit train travels along the prefabricated steel-spring floating-slab-track bed at different speeds, the wheel-axle lateral force, wheel-rail vertical force, the derailment coefficient, the wheel-weight reduction rate, and the lateral acceleration of the vehicle body are all less than the specified limits of Chinese code, thus fully meeting the safety requirements of train operation. (4) Appropriately increasing the vertical-support damping of the floating slab can improve the vehicle’s vertical dynamic performance, reduce the vertical displacement of the rail, and lower the vibration response of the floating slab. (5) Adding side-mounted vibration isolators at the joint of the floating slab could greatly improve the stability of the floating slab itself and appropriately reduce the vehicle’s vertical vibration response. Due to the optimization and establishment of relevant factors influencing the performance of prefabricated steel-string floating-slab track achieved in the study, the results obtained are particularly useful for setting safety, comfort, and stability requirements of the floating slab.